MarylandOnline’s Inter-Institutional Project to Train Higher Education Adjunct Faculty to Teach Online - Shattuck, Julie; Dubins, Bobbi; Zilberman, Diana (International Review of Research in Open and Distributed Learning, 2011)
This article reports on an inter-institutional project to design, develop, pilot, and evaluate a state-wide online training course for higher education adjunct faculty who are preparing to teach their first online course. We begin with a brief literature review to contextualize the stated problem the project sought to address: the need for quality, accessible training for online adjunct faculty. We then give background information to describe the environment in which the project was situated before detailing the process of designing and piloting the first iteration of the Certificate for Online Adjunct Teaching (COAT) course. Using a mixed-methods approach (surveys and reflection journals), data were collected from the adjunct faculty who took the COAT course, the COAT instructor, and the COAT design team. The results indicate that the pilot COAT course did meet the perceived needs and expectations of the course participants. We finish by discussing our plans for the next phase of this project.